2022
DOI: 10.1021/acsomega.2c01222
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Role of the Metal–Support Perimeter Region in Electrochemical NH3 Synthesis: A Density Functional Theory Study on Ru/BaCeO3

Abstract: The catalytic electrochemical synthesis of NH 3 on Ru/BaCeO 3 was investigated using density functional theory. The competition between NH 3 formation and the hydrogen evolution reaction (HER) is a key for a high NH 3 formation rate. Our calculations show that H adsorbs more strongly than N 2 at the Ru particle moiety, while the adsorption of N 2 is stronger than the H adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The synthesis of ammonia is greatly significant in industry and has continued to attract a great deal of interest. Because its mechanism on Ru catalysts has been thoroughly studied by experimental and theoretical studies, the reaction could provide a well-defined system for illustrating new theories and concepts. The surface science technique has been implemented to intuitively study the surface structure of catalysts and revealed that N 2 dissociation activity at the step site was 9 orders of magnitude higher than that on the terrace site . Further theoretical calculations combined with experiments illustrated that the step site with the B5 structure has the highest activity and is the real active center .…”
mentioning
confidence: 99%
“…The synthesis of ammonia is greatly significant in industry and has continued to attract a great deal of interest. Because its mechanism on Ru catalysts has been thoroughly studied by experimental and theoretical studies, the reaction could provide a well-defined system for illustrating new theories and concepts. The surface science technique has been implemented to intuitively study the surface structure of catalysts and revealed that N 2 dissociation activity at the step site was 9 orders of magnitude higher than that on the terrace site . Further theoretical calculations combined with experiments illustrated that the step site with the B5 structure has the highest activity and is the real active center .…”
mentioning
confidence: 99%